A conceptualisation of scale-up and sustainability of social innovations in global health: a narrative review and integrative framework for action - Marietou Niang; Hassane Alami; Marie-Pierre Gagnon; Sophie Dupéré (Taylor & Francis Group, 2023)
Background The scale-up and sustainability of social innovations for health have received increased interest in global health research in recent years; however, these ambiguous concepts are poorly defined and insufficiently theorised and studied. Researchers, policymakers, and practitioners lack conceptual clarity and integrated frameworks for the scale-up and sustainability of global health innovations. Often, the frameworks developed are conceived in a linear and deterministic or consequentialist vision of the diffusion of innovations. This approach limits the consideration of complexity in scaling up and sustaining innovations. Objective By using a systems theory lens and conducting a narrative review, this manuscript aims to produce an evidence-based integrative conceptual framework for the scale-up and sustainability of global health innovations. Method We conducted a hermeneutic narrative review to synthetise different definitions of scale-up and sustainability to model an integrative definition of these concepts for global health. We have summarised the literature on the determinants that influence the conditions for innovation success or failure while noting the interconnections between internal and external innovation environments. Results The internal innovation environment includes innovation characteristics (effectiveness and testability, monitoring and evaluation systems, simplification processes, resource requirements) and organisational characteristics (leadership and governance, organisational change, and organisational viability). The external innovation environment refers to receptive and transformative environments; the values, cultures, norms, and practices of individuals, communities, organisations, and systems; and other contextual characteristics relevant to innovation development. Conclusion From these syntheses, we proposed an interconnected framework for action to better guide innovation researchers, practitioners, and policymakers in incorporating complexity and systemic interactions between internal and external innovation environments in global health.